Concepções de infância e de educação infantil que permeiam a prática docente - Pinheiro, Maria Margarida (2008)
This investigation proposes to analyze the teaching practice in the Child Education, considering the childhood and the Child Education conceptions declared by the teachers. It was opted as methodological approach the qualitative conception of research, marking a critical perspective of the subjects, and their relations in the educational processes. It was privileged as instruments of construction of the data, the observation of the practices of the teachers developed in the ordinary day, the semistructured interviews, and the documental analysis to complement information, through the developing report of the students, done by the teachers in the end of the teaching year. This way, from the understanding of the childhood in a social perspective, and historically constructed, considering the concrete children insertion in the social reality and the child as a whole subject and by rights, it was developed the interpretative analysis of the data. The investigated reality showed that the childhood conceptions linked to the comprehension of child and child development, declared by the teachers, subjects of the research, have been associated, in some aspects, to the present thought of thinking and acting in relation to the small child, evidencing, consequently, several limitations of pedagogical order, and the demanding evidence of a bigger development of the teachers about the question.